Infant and young child feeding practices and child undernutrition in Bangladesh: Insights from nationally representative data - Zongrone, Amanda; Winskell, Kate; Menon, Purnima (Cambridge University Press, 2012)
To determine the association between indicators of infant and young child feeding (IYCF) and anthropometric measures of nutritional status among children aged 0–23 months in a nationally representative data set.Data from the 2007 Bangladesh Demographic and Health Survey were used. Analyses were conducted using multiple linear regression and logistic regression analyses adjusted for the complex survey design of the survey, controlling for child, maternal and household characteristics, and including regional dummy variables.Bangladesh.Pairs (n 2096) of last born infants and their mothers.Exclusive breast-feeding under 6 months of age was associated with higher weight-for-height Z-score (effect size (ES) = 0·29; P < 0·05). Appropriate complementary feeding in children aged 6–8 months was associated with higher height-for-age Z-score (HAZ; ES = 0·63; P < 0·01) and higher weight-for-age Z-score (WAZ; ES = 0·30; P < 0·05). Higher dietary diversity index (DDI) was associated with higher HAZ (ES = 0·08; P < 0·01 for every 1 point higher DDI) and higher WAZ (ES = 0·04; P < 0·05). Children who achieved minimum diet diversity had higher HAZ (ES = 0·20; P < 0·05). Logistic regression models confirmed that exclusive breast-feeding was protective against wasting and DDI was protective against stunting and underweight.Our results highlight the importance of IYCF practices as determinants of child growth outcomes in this context, and reinforce the need for interventions that address the spectrum of IYCF practices, from exclusive breast-feeding to age-appropriate complementary feeding, especially diet diversity, in efforts to improve nutrition of infants and young children.